Breakaway oxidation of Ti3AlC2 during long-term exposure in air at 1100 °C. (March 2016) - Li, Xichao; Zheng, Lili; Qian, Yuhai; Xu, Jingjun; Li, Meishuan
Highlights: Breakaway oxidation of Ti3 AlC2 occurs after oxidation at 1100 °C in air for 3171 h. The oxidation law changes from cubic to linear after the transition time. The critical Al content for selective oxidation is 5.99% lower than initial value. Ti3 AlC2 maintains its crystal structure after oxidation for 3250 h. Pores generated at the Al2 O3 /Ti3 AlC2 interface reduce the oxide scale adhesion. Abstract: Catastrophic breakaway oxidation of Ti3 AlC2 occurs during long-term oxidation at 1100 °C in air up to 4000 h. Correspondingly, the oxidation kinetics transforms from cubic law to linear law. The transition time is about 3171 h, and the corresponding critical Al content is about 5.99% lower than the initial content. Afterwards, Ti and C start to be oxidized instead of selective oxidation of Al, and Al2 O3 scale loses its protectiveness. Meanwhile, voids generated at the Al2 O3 /Ti3 AlC2 interface reduce the oxide scale adhesion. After 3250 h oxidation, Ti3 AlC2 still maintains its crystal structure, indicating the capability of bearing great Al lack.